Using Short Stories in Teaching Reading Comprehension of Narrative Text to the First-Year Students of SMK Negeri Campalagian - Emelia Mustika Efendi; Baso Jabu; Amra Ariyani (Journal of Excellence in English Language Education, 2022)
The objective of this research was to determine whether or not the use of short stories is effective in teaching reading comprehension of narrative text to the first-year students of SMK Negeri Campalagian. This research used cluster random sampling with 25 students of class X TKJ (Teknik Komputer dan Jaringan). This research used a pre-experimental design consisting of two cycles, namely pre-test, and post-test. The data was obtained through a reading comprehension test which consisted of 30 questions that aimed to determine students’ ability to comprehend a text. In analyzing the data, the researchers used a t-test to find out whether there was a significant difference before and after students were given treatment using short stories. The results of statistic calculations showed a significant difference between the pre-test and post-test. This was indicated by the t-test value which is greater than the t-table value (26.796>1.711). Based on the result, it can be obtained that the use of short stories is effective in teaching reading comprehension of narrative text to the first-year students of SMK Negeri Campalagian.